2007
DOI: 10.1007/s10608-007-9150-1
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Intentions Facilitate Response Inhibition in Children with ADHD

Abstract: Attention Deficit/Hyperactivity Disorder (ADHD) is associated with action control problems such as failure to inhibit inappropriate responses. Two studies investigated whether self-regulation by implementation intentions (if-then plans; Gollwitzer, P. M. (1999). Implementation intentions: Strong effects of simple plans. American Psychologist, 54, 493-503) facilitates response inhibition in children with ADHD. In Study 1, children with ADHD who furnished a suppression goal with implementation intentions improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 56 publications
(58 reference statements)
5
65
0
2
Order By: Relevance
“…The second study compared the performance of ADHD children with and without psychostimulant medication: a combination of if-then plans and medication resulted in the highest level of inhibition performance in children with ADHD. Again, replicating the findings of Study 1, children with ADHD showed a superior inhibition performance when having made an if-then plan as compared to merely forming a goal intention even without any medication (Gawrilow & Gollwitzer, 2008). Finally, a recent study showed that the beneficial effects of if-then plans in children with ADHD also pertain to delay of gratification, a performance that rests on effective motivation control (Gawrilow, Gollwitzer, & Oettingen, in press).…”
supporting
confidence: 62%
See 4 more Smart Citations
“…The second study compared the performance of ADHD children with and without psychostimulant medication: a combination of if-then plans and medication resulted in the highest level of inhibition performance in children with ADHD. Again, replicating the findings of Study 1, children with ADHD showed a superior inhibition performance when having made an if-then plan as compared to merely forming a goal intention even without any medication (Gawrilow & Gollwitzer, 2008). Finally, a recent study showed that the beneficial effects of if-then plans in children with ADHD also pertain to delay of gratification, a performance that rests on effective motivation control (Gawrilow, Gollwitzer, & Oettingen, in press).…”
supporting
confidence: 62%
“…Therefore, both studies represent not only a replication but also an extension of previous studies observing the beneficial if-then plan effect on tasks assessing the executive function deficit of reduced inhibition (Gawrilow & Gollwitzer, 2008) and motivation control deficit of reduced delay of gratification (Gawrilow et al, in press). …”
Section: Overview Of the Present Studiesmentioning
confidence: 60%
See 3 more Smart Citations